solve 2(x + 1/x)^2 - 3(x-1/x)-8=0

Dear student,

2(x + 1x)² - 3(x - 1x) - 8 = 02*(x² +1x)² - 3(x² - 1x) - 8 = 02(x² + 1)²x²-3(x² - 1)x-8 = 02(x4 + 2x² + 1) - 3x(x² - 1) - 8x² = 02x4 +4x² + 2 - 3x3 +3x - 8x² = 02x4 - 3x3 - 4x² +3x+ 2 = 0Value of the given polynomial is zero at x = 1. So, (x - 1) is one of the factors.2x3(x - 1)-x²(x - 1)-5x(x - 1)-2(x - 1) = 0(x - 1)(2x3 - x² - 5x - 2) = 0Now, let us consider the polynomial: (2x3 - x² - 5x - 2). (x+1) will be the factor of this polynomial.(2x3 - x² - 5x - 2)2x²(x + 1)-3x(x + 1)-2(x + 1)(x + 1)(2x² - 3x- 2)(x + 1)(2x² - 4x + x - 2)(x + 1)(2x(x -2) + 1(x - 2))(x + 1)(x - 2)(2x + 1)So, 2x4 - 3x3 - 4x² +3x+ 2 = 0 can be written as:2x4 - 3x3 - 4x² +3x+ 2 = 0(x + 1)(x - 2)(2x + 1)(x - 1) = 0x = ±1, 2, -12 
Regards

  • -1
What are you looking for?